Highly Active and Stable Fe-N-C Oxygen Reduction Electrocatalysts Derived from Electrospinning and In Situ Pyrolysis - Xuelian Yan; Yucen Yao; Yuan Chen (Nanoscale Research Letters, 2018)
Abstract High-performance electrocatalysts for the oxygen reduction reaction (ORR) are essential in electrochemical energy storage and conversion technologies. Fe-N-C electrocatalysts have been developed as one of the most promising alternatives to precious metal materials. Current M-N-C electrocatalysts usually are derived from high-temperature thermal treatment of a nitrogen-containing polymer or metal–organic frameworks (MOFs). Here, we developed Fe-N-C mesoporous nanofibers with low-cost urea and FeCl3 as the nitride and iron source; the electrocatalysts with abundant Fe-Nx active sites and large surface area were synthesized via electrospinning, in situ pyrolysis, and acid treatment process. The use of sealing conditions in the calcination process can effectively improve the nitrogen species content in the catalyst, which is important for improving performance. The as-prepared electrocatalyst material manifests well electrocatalytic performance for ORR in alkaline electrolyte (onset potential of 0.93 V and half-wave potential of 0.82 V); meanwhile, the electrocatalyst expresses good stability and methanol tolerance. This work may provide new thought for developing high-performance ORR electrocatalysts.